Perl 6 Essentials - Allison Randal (O'Reilly /Shroff Publishers, 2003)
Perl 6 Essentials is a sneak preview of Perl 6, the widely anticipated rewrite of the Perl programming language. Still in development, the Perl 6 project is a community-based effort to keep Perl vibrant well into the 21st century. This book covers the development not only of Perl 6 syntax but also of Parrot, the language-independent virtual machine developed as part of the Perl 6 design strategy.